2020
DOI: 10.18061/bhac.v4i2.7617
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chronotype and Grit on Lifestyle and Physical Activity

Abstract: Background:  The chronotype of a person refers to an individual's natural sleep-wake cycle and whether that individual prefers morning or evening activities, and grit is an individual's perseverance and passion for long-term goals.Aim: The purpose of this study was to investigate the relationship between grit, chronotype, physical activity, and leading a healthy lifestyle in college-age students.Methods:  Health and fitness data (i.e., chronotype, grit, lifestyle assessment score, and daily steps) from 431 fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
3
3
1
Order By: Relevance
“…A higher level of grit was related to a higher number of physical activity days per week among children. Our results are similar to those of a study by Allee et al [29], in which a higher level of grit among children was associated with a higher level of physical activity. According to a previous study [7], family culture and parental policies on physical activity can substantially promote healthy physical activity in children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…A higher level of grit was related to a higher number of physical activity days per week among children. Our results are similar to those of a study by Allee et al [29], in which a higher level of grit among children was associated with a higher level of physical activity. According to a previous study [7], family culture and parental policies on physical activity can substantially promote healthy physical activity in children and adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, poorer self-regulation skills in late-type students may contribute to late bedtimes and short nocturnal sleep on school nights. In contrast to previous studies (21)(22)(23)(24)(25)(26)(27)(28)(29), chronotype was not associated with self-control, intrinsic motivation, achievement learning goals, conscientiousness, and grit. However, earlier work defined chronotype based on diurnal preference (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The survey comprised about 20 instruments/scales for assessing non-cognitive constructs that are relevant for students' learning. We limited our analysis to constructs that have been shown to associate with students' morningness/eveningness preference (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including self-regulation, self-control, intrinsic motivation, achievement learning goals, conscientiousness, and grit (Supplementary Methods). The survey was offered to all students who enrolled in the first semester of the 2018/19 academic year, and it was completed prior to the start of classes in August, 2018.…”
Section: Psychological Correlates Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that although exercise times were not statistically different in the present study, exercise frequency and chronotypes may have a relationship such that a greater change in physical activity corresponds to a greater change in chronotype score. This is in line with previous research that indicates correlations between amount of physical activity and chronotypes [ 21 , 22 ]. For example, one study reported associations between ET scores and low leisure time physical activity [ 21 ].…”
Section: Discussionsupporting
confidence: 93%